Primary Carcinoid Tumour of the Kidney: A Review of the Literature - Omiyale, Ayodeji O. (Hindawi Publishing Corporation, 2013)
Context. Primary renal carcinoid tumours are rare. Their pathogenesis is unknown and the clinical presentation is similar to other renal tumours thus posing diagnostic dilemmas for clinicians. Objectives. To review the literature for case reports of primary renal carcinoids. Methods. Literature was extensively searched for case reports for primary renal carcinoids. Reports of metastatic carcinoids to the kidneys were excluded. Results. Approximately less than 90 cases of primary carcinoid tumours of the kidney have been reported in the literature. A total of 29 cases of primary renal carcinoids were reviewed. The mean age of presentation was 48 years (range 29–75) with both right kidney (48.3%) and left kidney (44.8%) being equally affected. 28.6% of the cases reviewed were diagnosed as an incidental finding. The mean followup time was 20 months with 73.1% of patients without evidence of disease after surgical treatment (radical or partial nephrectomy). Primary carcinoid tumours of the kidney are often well differentiated tumours. They are often misdiagnosed because of their rarity and similar presentation with other renal tumours. Conclusions. Primary carcinoid tumours of the kidney are rare tumours with an indolent course with frequent metastasis. Metastatic work up and followup is required in their management.